Learning management of machining engineering skill concentration in improving the competence of smk students - Agus Wahyu; Deti Rostini; Abdul Holik (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Facing the increasingly stringent era of globalization, Vocational High Schools have an important role in preparing students who are ready to face the challenges of an increasingly competitive world of work. The purpose of this study is to obtain an overview and analyze the learning management of the Machining Engineering Concentration of Expertise in improving the competence of vocational students. This research uses a qualitative approach with descriptive research methods. The results of the study showed that (1) the learning planning of KK TPM has been carried out well, the curriculum as a learning guide is in accordance with applicable regulations, there are annual programs, semester programs, lesson schedules and teaching modules that refer to the curriculum. (2) The organization of KK TPM learning has been well implemented, there is a division of teaching duties of teachers according to their competence, teachers guide students in learning, students collaborate in their groups working on learning projects and there is support from the world of work / industry which acts as a guest teacher in learning. (3) Implementation of learning KK TPM learning has been carried out well seen in the opening activities, core activities and closing activities of learning are implemented well in accordance with lesson planning. (4) Supervision of KK TPM learning has been carried out well, there is a learning assessment, learning reflection and follow-up in improving the quality of learning. (5) The obstacles faced in learning KK TPM are the limited factors of the machines owned. (6) The solution in overcoming the obstacles faced is setting an effective machine use schedule, using simulator learning media in the form of applications on android phones or computers, collaborating with the world of work / industry in carrying out teaching factory activities in collaboration with industries involving students, and having guest teachers / practitioners from the world of work / industry in learning. This study can be concluded that the learning management of the concentration of machining engineering expertise has been carried out in accordance with planning, organizing, implementing, and supervising. However, there are obstacles in terms of the lack of practical learning facilities owned according to standards and solutions in overcoming these obstacles are using simulator learning media and also collaborating with the world of work / industry in supporting learning.